Systematic Literatur Review : Integrasi Literasi Matematika Pada Kurikulum Australia - Widiyastuti, Erni; Junaedi, Iwan; Mulyono, Mulyono (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2025)
Mathematical literacy, as defined by the OECD, encompasses the ability to formulate, use, and interpret mathematics in various real-life contexts.This study aims to analyze how mathematical literacy is integrated into the Australian curriculum, given the importance of this competency in 21st-century education. Utilizing a Systematic Literature Review (SLR) approach, this study identifies, analyzes, and synthesizes relevant articles from the Scopus database .Analysis of these articles revealed that mathematical literacy is integrated through four main approaches. First, the development of new curriculum elements, such as linking numeracy with interdisciplinary concepts, enhances the relevance of learning. Second, the use of data from standardized tests, such as NAPLAN, supports data-driven interventions, although this approach is often mechanistic. Third, context- and culture-based learning, including the use of interdisciplinary activities and early childhood games, increases student engagement. Fourth, teacher training is pivotal to the successful implementation of integration strategies.This study provides conceptual and practical insights for developing inclusive, evidence-based, and diversity-responsive curricula. However, its reliance on literature necessitates further studies to evaluate the direct implementation of these strategies in Australian schools. The findings are expected to support flexible and effective educational policies to improve students’ mathematical literacy.